Latihan Calf Muscle Endurance Pada Cidera Rupture Tendon Achilles: Sebuah Studi Kasus - Imam Fadli Muhammad (Journal of Health and Therapy, 2022)
This study aims to prove the effect of calf muscle endurance exercise on Achilles tendon repure injuries. This research is a case study conducted at a physiotherapy clinic in Surakarta, namely a 31-year-old football athlete who suffered a ruptured Achilles sinistra tendon. Pain measurement is done with VAS (Visual Analoge Scale). The results showed that giving calf muscle endurance exercise for ruptured achilles tendon injuries was able to reduce pain levels.